A study on customers satisfaction towards Ar Rahn pawn Broking-i: Bank Kerjasama Rakyat at Jalan Tangsi Branch Kuala Lumpur / Noor Hafizah Ismail Suhaimy - Ismail Suhaimy, Noor Hafizah (Faculty of Business and Management, 2010)
This is a prospective study on customers satisfaction towards Ar Rahn PawnBroking-i. at Bank Rakyat Jalan Tangsi branch. Questionnaires and interview method has been used in order to get the information for this study. In this study, the customers of Bank Rakyat which is Ar Rahn Pawn Broking will be the sample target. The researcher personally distributed the questionnaire to70 respondents selected randomly and only 50 respondents will be chosen as sample for this study. They are 50 customers of Bank Rakyat who deals with Ar Rahn Pawn Broking- i at Jalan Tangsi Branch. The data obtained from the chosen 50 respondents will be analyzed using PSS. The gathered data from the research process will go through several analyses; hence the result of this study will be interpreted. The information obtained will then help to achieve the objective of the study that conducted at the BankRakyat Jalan Tangsi branch. Out of 50 respondents 64% are female, 38% are Malay, 32% are Indians,18% are Chinese and 12% are other ethnicity (Sabah and Sarawak). Majority of them (62%) earned about RM 1001 to RM 3000 and only 10% are housewife.42% of the respondent gained the information about the Ar Rahn service through word by mouth. More than 90% of the respondent satisfied with the Ar Rahn services in terms of staff attitude, quality of information provided and so forth. They will recommend this service at this branch to their friends.